A graph-based approach for unpacking construction sequence analysis to evaluate schedules. (April 2022) - Hong, Ying; Xie, Haiyan; Hovhannisyan, Vahan; Brilakis, Ioannis
Highlights: This study proposed a graph-based method to find the most time-efficient construction sequence. Overall, 236 frequent sequences were found, and 90 sequences were related to onsite works. 36% of onsite sequences are related to rebar-formwork-concrete activities . Results help generate schedules for critical building elements and support construction process management. Abstract: Construction schedules can mitigate delay risks and are essential to project success. Yet, creating a quality construction schedule is often the outcome of experienced schedulers, and what makes it harder is the fact that historic information including decision reasoning was not documented and disseminated for future use. This study proposes a graph-based method to find the most time-efficient construction sequence from historic projects to improve scheduling productivity and accuracy. The proposed method captured the textual, numerical, and graphical features of construction schedules, and was validated on 353 construction schedules obtained from a Tier-1 contractor in the UK. The results indicate that earthwork sequences can be finished in 4.0% of the project time on average, but earthwork sequences are the least time-efficient ones in a construction project (29% delayed), particularly in road construction (88% delayed). This study compared the time efficiency of sequences learned from previous projects with case study sequences. Results indicated that frequent sequences learned from past projects are 26.7% closer to the actual schedule than the planned ones. Results of this study could assist inexperienced schedulers to create more quality construction schedules and project managers to benchmark project performances.